2003
DOI: 10.1182/blood-2002-08-2396
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-1–dependent neutrophil transmigration is independent of monolayer PECAM-1 signaling or localization

Abstract: Platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31), a tyrosine phosphoprotein highly expressed on endothelial cells and leukocytes, is an important component in the regulation of neutrophil transendothelial migration. Engagement of endothelial PECAM-1 activates tyrosine phosphorylation events and evokes prolonged calcium transients, while homophilic engagement of neutrophil PECAM-1 activates leukocyte ␤-integrins. Although PECAM-1 modulates polymorphoneutrophil transmigration via homophilic PECAM-1-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 64 publications
4
54
0
Order By: Relevance
“…A recent report (O'Brien et al 2003) describes five mechanisms by which CD31 could modulate the neutrophil migration across endothelial cell monolayers that is induced by cytokines (e.g., IL-1␤). The authors also note that transendothelial migration induced by neutrophil chemoattractants (LTB 4 ) or chemokines (IL-8) is CD31-independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report (O'Brien et al 2003) describes five mechanisms by which CD31 could modulate the neutrophil migration across endothelial cell monolayers that is induced by cytokines (e.g., IL-1␤). The authors also note that transendothelial migration induced by neutrophil chemoattractants (LTB 4 ) or chemokines (IL-8) is CD31-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, attachment of leukocytes to endothelium is not dependent on CD31, whereas transmigration of leukocytes is, at least for certain stimuli. Blocking antibodies could also act by interfering with cell signaling mechanisms (Newton-Nash and Newman 1999; Henshall et al 2001;Ilan et al 2001;Newman et al 2001;O'Brien et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies-For a custom-made anti-moue Ninjurin1 antibody, rabbits were immunized with keyhole limpet hemocyanin-conjugated synthetic peptide-bearing mouse Ninjurin1 residues 26 -37 (Ab 26 -37 ) and 1-15 (Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] ) following standard procedures (Peptron, Inc. and Abfrontier, Inc.); these antiNinjurin1 antibodies were purified in each case with antigenspecific affinity chromatography. The isotype rabbit IgG purified with a Protein A column (Upstate Biotechnology) from the serum of normal rabbits was used for the in vivo blocking experiment in the EAE model.…”
Section: Methodsmentioning
confidence: 99%
“…Each siRNA was transfected in Raw264.7 cells by Nucleofector (Amaxa) at a concentration of Ͻ200 pmol per sample. After 24 h, the Ninjurin1 knockdown efficiency was determined by Western blotting of anti-GFP and the custommade anti-Ninjurin1 antibody (Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, initial sPECAM-1 might be of predictive value for the short-term outcome of stroke ( Zaremba and Losy, 2002b). O'Brien et al(2003) demonstrated that PECAM-1 mediates neutrophil migration through IL-1 beta stimulated endothelial cells. It has shown that hyperhomocysteinemia at moderate level activates human monocyte and induces cytokine expression including tumor necrosis alpha, IL-1 beta, IL-6, IL-8, and IL-12 (Su et al, 2005).…”
Section: Folate Deficiency and Platelet Endothelial Cell Adhesion Molmentioning
confidence: 99%